Factors affecting work-life balance and psychological resilience levels of nurses working in internal clinics during COVID-19 - Korkmaz Aslan, Tuba; Burucu, Rukiye; Akdoğan, Yunus (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. COVID-19 intensity has affected both the psychology of the nurses and the balance established between their work and social lives. In this study, it was aimed to examine the work-life balance and psychological resilience levels of nurses. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Four Hundred and seventy two nurses, working in various hospitals and internal units in Turkey, voluntarily participated in the study. Data was collected online using the Work-Life Balance Scale, Brief Psychological Resilience Scale, and the Personal Information Form. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The sub-dimensions of the work-life balance scale include allocation of time for yourself (β=1.892; p<0.001), life merely being based on work (β=-0.513; p<0.05) and work-life balance; affect the psychological resilience score (β=-0.364; p<0.05). Based on this, devoting time for yourself has a positive effect on psychological resilience, while others have a negative effect. The total score of the nurses on work-life balance is 51.51±7.22 and their psychological resilience score is 15.27±3.93. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Psychological resilience is affected by educational status, marital status, having children, and working schedule; work-life balance is affected by educational status, marital status, having children, income levels, and working schedule; while work-life balance sub-dimensions are affected by education, marital status, having children, income levels, place of work and working schedule. Both work-life balance and its sub-dimensions affect the psychological resilience of nurses.